2015
DOI: 10.1016/j.biopsych.2014.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous Oxide for Treatment-Resistant Major Depression: A Proof-of-Concept Trial

Abstract: This proof-of-concept trial demonstrated that nitrous oxide has rapid and marked antidepressant effects in patients with TRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
238
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(245 citation statements)
references
References 49 publications
5
238
1
1
Order By: Relevance
“…This NMDA receptor blocker may act at least in part by decreasing the high firing rate state of attractor networks by reducing transmission in the recurrent collateral excitatory connections between the neurons (Deco et al, 2013;Rolls, 2012;Deco, 2010, 2015;Rolls et al, 2008c). Another NMDA receptor blocker, nitrous oxide, has also been shown to have an antidepressant effect, though the therapeutic use of nitrous oxide is not recommended because it produces vitamin B12 depletion (Nagele et al, 2015). Electroconvulsive therapy (ECT), which may have antidepressant effects, may also knock the non-reward system out of its attractor state, and this may contribute to any antidepressant effect.…”
Section: Evidence Consistent With the Theorymentioning
confidence: 99%
“…This NMDA receptor blocker may act at least in part by decreasing the high firing rate state of attractor networks by reducing transmission in the recurrent collateral excitatory connections between the neurons (Deco et al, 2013;Rolls, 2012;Deco, 2010, 2015;Rolls et al, 2008c). Another NMDA receptor blocker, nitrous oxide, has also been shown to have an antidepressant effect, though the therapeutic use of nitrous oxide is not recommended because it produces vitamin B12 depletion (Nagele et al, 2015). Electroconvulsive therapy (ECT), which may have antidepressant effects, may also knock the non-reward system out of its attractor state, and this may contribute to any antidepressant effect.…”
Section: Evidence Consistent With the Theorymentioning
confidence: 99%
“…These results have now been replicated in numerous observational and clinical trials (see Krystal et al, 2013 for a review). Moreover, several other drugs that work as NMDA antagonists including lanicemine (Sanacora et al, 2014), memantine (Kollmar et al, 2008) and nitrous oxide (Nagele et al, 2014) have all shown antidepressant properties. Furthermore, a range of neuroimaging techniques have recently been employed to assess the effects of ketamine on brain amino acid neurotransmitter levels (Salvadore et al, 2011) with a view to stratifying patients into response groups.…”
mentioning
confidence: 99%
“…One recently published randomized, blind, placebocontrolled crossover pilot study compared the antidepressant effects of inhaled nitrous oxide (administered over 1 h) with placebo in patients with TRD (n = 20). 31 Nitrous oxide rapidly decreased symptoms of depression within 2 h; these effects were sustained for at least 24 h. Response to nitrous oxide was 20%, and remission was 15%. Side effects were mild to moderate in nature, with no dissociation or psychotomimetic side effects appreciated.…”
Section: Novel Therapeutics: Review Glutamatergic Modulatorsmentioning
confidence: 96%